PENINGKATAN PROSES DAN HASIL BELAJAR IPA MELALUI MODEL PROBLEM BASED LEARNING SISWA SEKOLAH DASAR - Siti Patimah; Megawati Megawati; Puput Wahyu Hidayat; Randi Eka Putra (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
The problem in this study is the lack of student learning outcomesin science subjects, because the learning process only uses monotonous methods, the aim of this research is to improve the process and results of science learning using the problem-based learning model. This research is a classroom action research, which consists of two learning cycles. Each cycle consists of planning activities, implementation of actions, observation and reflection. The subject of this research is class IV, namely 16 students.The results of this study show that the teacher's activity in cycle I, meeting I, reached 60% at meeting II, cycle II increased to 75%. During the learning process using the PBL model in the first cycle the first meeting reached 76% and the second meeting 82% Then in the second cycle the first meeting reached 86% and the second meeting reached 88%. In the assessment of student learning outcomes using the PBL model in cycle I, the learning outcomes of students who completed reached 56% (9 people) and those who did not complete reached 43%. Whereas in cycle II the student learning outcomes that were completed reached 81% (13 people) and those that were incomplete were only 18.75% (3 people).